Effectiveness of Combining Oketani and Oxytocin Massage on The Breastmilk Production - Triana Indrayani; Risza Choirunnisa; Orachorn Lumprom (IJNP (Indonesian Journal of Nursing Practices), 2022)
Background: The percentage of exclusive breastfeeding for babies aged 0-5 months was 71.58% in 2021. This figure is still below the target of 80%. Meanwhile, the coverage of exclusive breastfeeding in West Java was recorded at 77.00% in 2022. Breastfeeding revolves around two mechanisms, namely, production and release. Objective: To determine the effect of the combination of oketani massage and oxytocin massage on breastmilk production in postpartum mothers. Methods: This research was conducted from July to November 2022 at the L TPMB. This study utilized a quantitative approach with a quasi-experimental design using a pre and post-test with a control design. The sample consisted of 100 respondents divided into experimental and control groups. In this case, the intervention was given to the experimental group in the form of oxytocin massage and oketani massage 1 to 2 times a day for 3 days for 3-5 minutes. Meanwhile, the control group was only given oxytocin massage treatment. The instrument used in this study was the Observation Sheet Procedure to identify the breastmilk production in postpartum mothers on day 1 and was measured again on day 7 through the smooth release of breastmilk. In addition, the instrument was made by the researcher according to Standard Operation Procedures. The analysis used was the man Whitney test. Result: Oketani massage could be performed as an independent and routine prophylactic intervention. Conclusion: The combination of oketani massage and oxytocin massage had a significant effect on breastmilk adequacy.